Response of mechanical properties of A356 alloy to continuous rheological extrusion Al-5Ti-0.6C-xCe alloy addition upon different Ce contents - Da Teng; Guangzong Zhang; Shuo Zhang; Junwen Li; Renguo Guan (Journal of Materials Research and Technology, 2023)
A356 alloy is a commonly used casting Al-Si alloy. Because of the excellent fluidity, air-tightness and thermal resistance, it is usually used as castings with complex structure. However, due to the coarse α-Al grains and needle-like phases, the defects including shrinkage cavity and porosity can easily be formed, which reduce the mechanical properties of the castings and lead to the lower safety factor. In this paper, Al-5Ti-0.6C-xCe (x = 0, 0.5, 1.0, 1.5 and 2.0 wt%) master alloys have been prepared by fluorine-salt method combined with the continuous rheological extrusion (CRE) technology. The response of mechanical properties of A356 alloy to the CRE Al-Ti-C-Ce alloys addition upon different Ce contents was investigated. Results showed that, with the increasing Ce content from 0 to 2.0 wt%, the average grain size of α-Al and length of coarse needle-like phases in A356 alloy changed nonmonotonically. When the Ce content was 1.0 wt%, the best refined structure was obtained. The tensile strength, yield strength and elongation of refined A356 by CRE Al-5Ti-0.6C-1.0Ce master alloy were 290.45 MPa, 238.27 MPa and 2.80%, respectively. The introduction of master alloys with different Ce contents promoted the refinement of grain and coarse needle-like phase in A356 alloy, which further improved the mechanical property of the alloy.